INTERNET PARENTING SEBAGAI KONTROL DALAM PENGGUNAAN INTERNET PADA REMAJA - Destari, Mutia Riani; Elmanora; Hamiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
This study aims to analyze the correlation between internet parenting and adolescent internet behavior. Data was collect using self-report techniques from May to June 2020. This study involved 235 students in one of junior high school, who were randomly selected. The instrument for measuring internet parenting was the Factor Analysis of Mediating Rules and Practices (Livingstone and Helsper, 2008), which consists of 24 statements. The instrument for measuring internet behavior was the Principal Component Analysis of the Internet Use Questionnaire (Johnson & Kulpa, 2006), which consists of 20 statements. The data collected was analyzed using descriptive statistics and inferential statistics, namely Pearson Correlation Coefficient. The results showed that internet parenting was included in the moderate category (54,5%). Internet behavior is included in the low category (55,3%). The results of correlation analysis show that internet parenting has a significant negative correlation with adolescent internet behavior (r=-0,223, p<0,01). These results indicate that the higher the attitude of parents in disciplining internet use in adolescents can reduce the frequency of adolescents using the internet. Thus, the implementation of internet parenting can be one way to reduce internet use in adolescents.